2015
DOI: 10.3390/ijms160614181
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Underlying Hull-Caryopsis Adhesion/Separation Revealed by Comparative Transcriptomic Analysis of Covered/Naked Barley (Hordeum vulgare L.)

Abstract: The covered/naked caryopsis trait of barley is an important agronomic trait because it is directly linked to dietary use. The formation of covered/naked caryopsis is controlled by an NUD transcription factor, which is involved in pericarp cuticle development. However, the molecular mechanism underlying this trait remains so far largely unknown. In this study, comparative transcriptomes of grains three weeks after anthesis of Tibetan Hulless barley landrace Dulihuang and covered barley Morex were analyzed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Organ fusion has been induced by expression of a fungal cutinase in Arabidopsis , where cuticular layers either remaned intact between cell walls, or walls of epidermal cells came in direct contact with each other [ 71 ]; organ fusion has also been induced by repression of WIN1/SHN1 , a gene with homology to Nud , in Arabidopsis and Tourenia fournieri [ 72 ]. The increase in abundance of compounds known to increase cuticle permeability in samples with the highest quality husk adhesion, supports the observations of Duan et al [ 43 ] that the process of husk adhesion is similar to organ fusion, and may be due to an increase in cuticle permeability. Although the present study suggests that cuticular wax composition has a role in the quality of husk adhesion, it is possible that the entire matrix of cell-wall, cutin and cuticular waxes contribute to husk adhesion.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Organ fusion has been induced by expression of a fungal cutinase in Arabidopsis , where cuticular layers either remaned intact between cell walls, or walls of epidermal cells came in direct contact with each other [ 71 ]; organ fusion has also been induced by repression of WIN1/SHN1 , a gene with homology to Nud , in Arabidopsis and Tourenia fournieri [ 72 ]. The increase in abundance of compounds known to increase cuticle permeability in samples with the highest quality husk adhesion, supports the observations of Duan et al [ 43 ] that the process of husk adhesion is similar to organ fusion, and may be due to an increase in cuticle permeability. Although the present study suggests that cuticular wax composition has a role in the quality of husk adhesion, it is possible that the entire matrix of cell-wall, cutin and cuticular waxes contribute to husk adhesion.…”
Section: Discussionsupporting
confidence: 88%
“…The long-chain alkane tritriacontane was also associated with good quality husk adhesion; n -alkanes have also been linked to cuticular permeability [ 66 ], however in tomato fruits, higher-chain alkanes with C 31 to C 34 were associated with lower cuticle permeability [ 67 ]. Organ fusion has been previously noted to be a similar phenotype to husk adhesion [ 43 ]. In the maize ad1 mutant, where the cell walls of floral parts adhere to each other, the cuticle appears to remain intact between the cell walls [ 41 ], similar in appearance to the cementing layer comprising the husk and pericarp surface cuticles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The covered/ naked phenotype is determined by expression of the Nud gene, which is typically deleted in naked barleys (Taketa et al 2008). However a recent study has shown that Nud is expressed at low levels in some Tibetan naked barley cultivars (Duan et al 2015), therefore differences in the quality of husk adhesion observed among these barley varieties may in fact be regulated by differential expression of Nud under the misting treatment. The misting treatment significantly increased the proportion of skinned grains without having an effect on ear length, floret number, grain number or grain weight.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the transcriptome of an organism is one of the most effective ways to investigate the structure and function of its active genes (Gutierrez-Gonzales et al 2013 ). Comparative analyses of transcriptomes using RNA-Seq techniques were performed by Duan et al ( 2015 ) to study the formation of covered/naked caryopsis in Tibetan hulless barley landrace Dulihuang and covered barley Morex. They identified 4031 differentially expressed genes (DEGs) in total and proposed Myb regulation of wax biosynthesis pathway to be involved in naked caryopsis.…”
Section: Introductionmentioning
confidence: 99%